2015
DOI: 10.1177/2156587215598039
|View full text |Cite
|
Sign up to set email alerts
|

A Review Study on Punica granatum L

Abstract: Punica granatum L (pomegranate) is a deciduous shrub, native to Iran. Nowadays, besides its use as a fruit, its medicinal properties have attracted the interest of researchers of many countries. Pomegranate fruit has medicinal properties such as antiinflammatory and antibacterial activities. The pomegranate seed oil has inhibitory effect on skin and breast cancers. The pomegranate seed oil has phytoestrogenic compounds and the fruit is rich in phenolic compounds with strong antioxidant activity. Ellagic acid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 59 publications
2
110
0
10
Order By: Relevance
“…For centuries, the pomegranate fruit has been used for its medicinal properties and is widely marketed for its purported health benefits (Shaygannia, Bahmani, Zamanzad, & Rafieian-Kopaei, 2016). The pomegranate fruit peel is a rich source of punicalins, punicalagins, and ellagic acids, but is an agricultural waste product (Akhtar, Ismail, Fraternale, & Sestili, 2015).…”
mentioning
confidence: 99%
“…For centuries, the pomegranate fruit has been used for its medicinal properties and is widely marketed for its purported health benefits (Shaygannia, Bahmani, Zamanzad, & Rafieian-Kopaei, 2016). The pomegranate fruit peel is a rich source of punicalins, punicalagins, and ellagic acids, but is an agricultural waste product (Akhtar, Ismail, Fraternale, & Sestili, 2015).…”
mentioning
confidence: 99%
“…Previous studies have also shown that pomegranate juice has the least antioxidant but the most anti‐mutation effects. In contrast, its methanolic extract showed the most antioxidant but the lowest antimutation activity (Shaygannia, Bahmani, Zamanzad, & Rafieian‐Kopaei, ). Hafiz et al evaluated the hepato‐protective and antioxidative effects of PPE on Plasmodium chabaudi ‐induced hepatic damage.…”
Section: Resultsmentioning
confidence: 99%
“…the lowest antimutation activity(Shaygannia, Bahmani, Zamanzad, & Rafieian-Kopaei, 2016). Hafiz et al evaluated the hepato-protective and antioxidative effects of PPE on Plasmodium chabaudi-induced hepatic damage.…”
mentioning
confidence: 99%
“…Pomegranate extracts contain anthocyanins, ellagitannins and hydrolyzable tannins, and oral administration of these extracts reduces UVB-induced carcinogenesis in mice (41,42). Ellagic acids contained in pomegranates exhibit antimutant, antiviral, antioxidant and skin-whitening activity and are already used in Japan as a food additive (43). It has also been suggested that punic acid in pomegranate seed oil may prevent 7,12-dimethylbenz(a)anthracene (DMBA)- and 12- O -tetradecanoylphorbol-13-acetate (TPA)-induced skin cancer (44,45).…”
Section: Discussionmentioning
confidence: 99%